(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article talks about ways to achieve high efficiency through the use of a leader’s management culture in an educational institution, as well as methods for managing the teaching staff, as well as the availability of sufficient recommendations so that the leader has good knowledge. modern educational technologies and constantly improve them, study management methods in groups. They say that he had to learn information about